BEHAVIOR OF CHOOSING CHINESE COMMUNITY IN KRANGGAN VILLAGE IN PRESIDENTIAL ELECTION AND VICE PRESIDENT IN 2019 - Triko - Wijayanto; Dewi - Erowati (Journal of Politic and Government Studies, 2020)
As a democracy the presidential election and vice president have always been the momentum that many people have always awaited to be able to convey the sovereignty of the people as a manifestation of the main ideals of a democratic country. The presidential and vice presidential elections in 2019 were followed by various layers of society, including the people of Chinese descent, which is now a minority society in Indonesia. The behavior of choosing Chinese community in Kranggan village in presidential election and vice president in 2019 is interesting to be researched because the number of minority and Chinese people are known as a society that is quite apathy with the political world in Indonesia. This research uses quantitative research methods and uses theory of vote behaviour as well as theory of political participation. The conclusion of this research will illustrate the behavior of selecting Chinese society and the participation rate of Chinese society in the presidential election in 2019.